Potency of 1 - deoxynojirimycin Compounds for Slowed Hydrolysis of Various Carbohydrates by Raw Enzymes of the Rumen Liquid - S. Syahrir; F. K. Tangdilintin; K. G. Wiryawan; A. Parakkasi; M. Winugroho (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2011)
Compound of 1- deoxynojirimycin (DNJ) in the mulberry leave extract (MLE) potentially hamper the hydrolysis process of various carbohydrates. This experiment aimed to study dynamic concentration of reductive sugar resulted from the hydrolysis of various carbohydrates by raw enzymes of the rumen liquid, with or without the addition of mulberry leave extract containing 1-deoxynojirimycin. Materials tested are maltose, sucrose, starch and cellulose. The result of the experiment showed that the addition of mulberry leave extract on the media with the substrate of maltose hampered the activity of maltase. It was concluded that MLE containing DNJ can be used as an agent of slow release mechanism of non-structural carbohydrates, especially maltose, in the rumen system.